Embedded foresight in RTD programs. (1st January 2002) - Salo, Ahti; Salmenkaita, Jukka-Pekka
In recent years, several countries have carried out large-scale technology foresight exercises. While these have been extensively discussed in the literature, less attention has been given to how foresight objectives are served through consultative processes which are not necessarily designated as "foresight" but nevertheless seek to provide direction to publicly supported research and technology development (RTD) efforts. Here, we address this question by examining Finnish RTD programmes in electronics and telecommunications where foresight processes have been enacted to build up capabilities for strategic flexibility and, more specifically, for the ability to change the direction of RTD efforts during the programme. We also argue that these processes may be crucial in conditions of rapid technological change.